Human Resources Consultants: What Digital Skills? - Andreia ANTUNES; Dora MARTINS; Susana SILVA & Cândida SILVA (Communications of International Proceedings, 2021)
The significant changes in the organisational environment and the frequent technological innovations that arose from the industrial revolutions over the centuries have a considerable impact on the labor market. The global economy has created a dynamic, competitive and complex environment, where organizations need to adjust and compete to achieve success. The Human Resources Consultancy sector must adjust its services and solutions to ensure organisational sustainability in the Digital Era and implement innovative mechanisms for the development of skills to offer a distinct value proposal in an increasingly globalized, and digital, market. This research’s main objective is to characterize the Human Resources consulting sector, identify the relational and technical challenges of professionals arising from digital transformation, and, finally, identify the skills required of Human Resources consultants in this digital age. A qualitative methodology was carried out within ten Human Resources Consultants, and data analyzed according to the Grounded Theory principles. The results of this study show that digital transformation is a significant challenge for the Human Resources Consulting sector, which needs to adapt its corporate culture to digital transformation and create a commitment to innovation and change. Moreover, the economic and social context, globalization, competitiveness, the market and customers’ demands, require redefining this sector’s strategy and redesigning business models based on ideas and methodologies that stand out. This result allows to start designing two other studies: one to understand the clients’ perception relatively to consultants’ actions and skills, and other to consolidate this study with a wider quantitative study.
Keywords: Human Resources; Consultancy; Consultants; Skills; Digital Transformation